Hubungan Pengetahuan, Sikap Ibu dan Dukungan Suami dengan Kelengkapan Pemberian Imunisasi Tetanus Toxoid (TT) Pada Ibu Hamil - Dameria Sitorus; Siti Aisyah; Rizki Amalia (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Tetanus Toxoid Immunization (TT) is an attenuated and purified tetanus germ toxin that is given to infants, children and mothers in an effort to provide protection against tetanus. This study aims to determine the relationship between knowledge, mother's attitude and husband's support with the completeness of giving Tetanus Toxoid (TT) immunization to pregnant women in the Tanjung Baru Public Health Center Work Area, OKU Regency in 2021. The design of this study is an analytical survey using a cross sectional research design. The population in this study were all third trimester pregnant women who had their pregnancy checked in January-July 2021, namely 38 respondents and the number of samples was 38 respondents. The sampling technique used is purposive sampling. Data analysis used Chi Square statistical test with Pvalue (0.05). The results of this study were from 20 respondents who had good knowledge with the completeness of TT immunization as many as 17 people (85.0%) with Pvalue = 0.02, from 21 respondents who had a positive attitude with completeness of TT immunization as many as 18 people (85.7%). with P-value = 0.01, and of the 21 respondents who had a positive attitude with completeness of TT immunization as many as 18 people (85.7%) with P-value = 0.01. Midwives are expected to increase knowledge to mothers about giving Tetanus Toxoid (TT) immunization so that they can improve the quality of service.